Paraguay : Fourth Review Under the Stand-By Arrangement and Request for Reduction and Rephasing of Access; Staff Report; Staff Statement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Paraguay. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The recent tightening of credit conditions in segments of mature financial markets abroad has not had an impact on Paraguay. The current mix of macroeconomic policies combined with favorable external conditions and the appreciation of the guarani, have facilitated strong program performance and a decline in core inflation over the past months. At the international level, there is a risk that a global slowdown associated with the credit tightening could spill over to emerging economies and to Paraguay's neighbors, which could affect Paraguayan exports.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet